PERAN KONSELOR LINTAS AGAMA DAN BUDAYA SEBAGAI DINAMIKA KOMUNIKASI ANTARBUDAYA [THE ROLE OF CROSS-FAITH AND CULTURAL COUNSELORS AS A DYNAMIC OF INTERCULTURAL COMMUNICATION] - Aprilianti, Eka; Avisor, Muhammad Khafif Aziwal; Lessy, Zulkipli (Acta Islamica Counsenesia: Counselling Research and Applications, 2023)
This research is motivated by the condition of Indonesia as a country which is rich in culture, and therefore Indonesia has different patterns of lives in society. So, there is a need for a facilitator who can mitigate the anxiety of the people. This study aims to find out how the role of cross-faith and cultural counselors play a significant role in the dynamics of intercultural communication. This research uses a literature study approach. Sources of data that are used as material for this research are books, journals, and internet sites related to the selected topic. In this study, after the data was collected, the data was analyzed to get conclusions. The results in this study are that counselors who are sensitive to religion and culture are those who must have an awareness of knowing their own culture in all respects. Therefore, it can be understood that what can influence the mindset, actions, and feelings of a counselee can come from every culture. A counselor must be able to find the right approach or according to the characteristics of the counselee and must not force the counselee to follow the cultural values that the counselor wants. Therefore, the role of the counselor must really understand the characteristics of the counselee in terms of religion and culture.